All unicyclic graphs of order n with locating-chromatic number n-3 - Edy Tri Baskoro; Arfin Arfin (Indonesian Journal of Combinatorics, 2021)
Characterizing all graphs having a certain locating-chromatic number is not an easy task. In this paper, we are going to pay attention on finding all unicyclic graphs of order n (⩾ 6) and having locating-chromatic number n-3.